Comparative Evaluation of Four Irrigating Solutions for the Removal of Calcium Hydroxide from Root Canal Walls: An In Vitro Study - Akanksha, Akanksha; Sharma, Deepak; Mathur, Rachit; Rajkumar, Anandan Aditya; Khajuria, Sameeha; Saladi, Hemanth (Journal of Neonatal Surgery, 2025)
Introduction: Calcium hydroxide [Ca(OH)₂] is widely used as an intracanal medicament due to its antimicrobial properties, but its remnants may compromise root canal sealing. This study compared the effectiveness of four irrigating solutions—3% sodium hypochlorite (NaOCl), 17% ethylenediaminetetraacetic acid (EDTA), saline, and MTAD—for Ca(OH)₂ removal using passive ultrasonic irrigation (PUI). Methods: Forty single-rooted human premolars were decoronated and prepared using the ProTaper Universal system. Ca(OH)₂ was placed for 7 days. Teeth were divided into four groups (n=10) based on final irrigant: NaOCl, EDTA, MTAD, and saline. Each irrigant was activated with PUI. Roots were split and examined under a stereomicroscope. Residual Ca(OH)₂ was scored (0–5) based on surface coverage. Data were analyzed using ANOVA and Tukey’s post hoc tests (p<0.05). Results: EDTA achieved the lowest mean score (1.08), indicating superior removal, followed by MTAD (2.71). NaOCl and saline were least effective (mean 4.00). Statistically significant differences were found among groups (p<0.05), especially in the apical third. Conclusions: 17% EDTA was the most effective solution for Ca(OH)₂ removal when combined with PUI. MTAD showed moderate efficacy, while NaOCl and saline were significantly less effective